NGHIÊN CỨU BIỂU HIỆN ENDO-GLUCANASE TÁI TỔ HỢP NGUỒN GỐC TỪ DNA METAGENOM VI KHUẨN DẠ CỎ DÊ Ở QUY MÔ BÌNH LÊN MEN 5 LÍT - Đào, Trọng Khoa; Đỗ, Thị Huyền; Trương, Nam Hải (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EXPRESSION OF RECOMBINANT ENDO-GLUCANASE DERIVED FROM BACTERIA INSIDE VIETNAM GOAT RUMEN IN 5-LITER BIO-REACTORCellulose is one of the three main components of lignocellulose and one of the world's largest reserves of biomass. Endo-glucanase is one of the three crucial enzyms in the hydrolysis process of cellulose into glucoses. The endo-glucanase gene has been mined by bioinformatics tools in next-generation sequencing data of metagenom DNA from bacteria residing in goat rumen. In previous study, the endo-glucanase gene was successfully recombinantly expressed in the E. coli Rosetta1 strain in flask, the expressed protein existed in the soluble form with good activity. In order to apply in bigger scale, endo-glucanase was investigated for expression in a 5-liter bio-reactor. The research results showed that the expressed protein reached about 1.5-1.7 mg/ml with crude activity of about 37-38 U/ml of fermentation solution. The endo-glucanase protein, after being purified by His-tag affinity chromatography column and salt-removed by membrane dialysis, has a fairly high activity of about 400 U/mg. This result showed potential for the application of endo-glucanase production on an industrial scale.